Longitudinally Measured Changes in Somnolence Severity With a Visual Analog Scale in a Randomized Lithium Versus Quetiapine-IR Study in Bipolar Disorder. Issue 3 (May 2019) - Gao, Keming; Su, Meilei; Ganocy, Stephen J.; Goto, Toyomi; Yuan, Chengmei; Fang, Fang; Conroy, Carla; Brownrigg, Brittany; Serrano, Mary Beth; Calabrese, Joseph R.
Abstract: Objective: The aim of this study was to use a visual analog scale (VAS) longitudinally measuring somnolence severity in patients with bipolar disorder. Methods: A data set of patients with bipolar spectrum disorders who were randomized to lithium or quetiapine-IR for 16 weeks was used. The somnolence severity was measured with a VAS from 0 to 100 (VAS based), and somnolence frequency was recorded according to incident report (incidence based) at each visit. The rates of VAS-based and incidence-based somnolence and changes in somnolence severity from baseline to the end of study were compared between the lithium and quetiapine groups. Longitudinal changes in somnolence severity were analyzed with linear regression analysis. Results: Of 42 patients randomized, only 3 scored 0 on the VAS at baseline. The rates of incidence-based and VAS-based somnolence were similar in the lithium and quetiapine-IR groups. The VAS change scores from baseline to each visit varied in both groups with significant decreases at weeks 6 and 12 in the quetiapine-IR group only. The decrease at week 6 in the quetiapine-IR group was significantly different from that in the lithium group. Patterns of changes in somnolence severity were inconsistent in both groups. A significant interaction between time course and the decrease in VAS scores was observed in the quetiapine-IR group, but not in the lithium group. Conclusions: Baseline somnolence was highly prevalent in patients with bipolar disorder. The change in somnolence severity was different between lithium-treated and quetiapine-treated patients. Quantifying somnolence longitudinally is important in clinical trials and practice.